+0  
 
0
110
1
avatar

For Pythagoras' theorem, a^2+b^2=c^2, prove that a+b>c

Guest Jun 2, 2017
Sort: 

1+0 Answers

 #1
avatar+77122 
+2

Let us first assume that  a + b  = c

 

Then

 

a^2   +  b^2  =  c^2

a^2  + b^2   =  ( a + b)^2

a^2  + b^2  =  a^2 + 2ab + b^2

0  =  2ab      which is impossible  since  a , b   are positive 

 

Next, assume that  a +  b  < c

Then.....there must be some positive n  such that  a + b  + n  =  c

So

a^2 + b^2  = c^2

a^2 + b^2   = (a + b + n)^2

a^2  + b^2  = a^2 + 2ab + 2an + b^2 + 2bn + n^2

0  =  2ab + 2an + 2bn + n^2      which is also impossible since a,b and n are positive

 

So....

a + b  = c   is false

a + b < c  is false

 

And the only thing left is that   a + b > c

 

 

cool cool cool

CPhill  Jun 2, 2017
edited by CPhill  Jun 2, 2017

20 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details